A short-term decision-making model for a price-maker distribution company in wholesale and retail electricity markets considering demand response and real-time pricing. (May 2020) - Moghimi, Farzad Hassanzadeh; Barforoushi, Taghi
Highlights: Proposing a new bi-level model for a strategic DisCo in electricity markets. Considering uncertainty of elastic demand at retail level under RTP mechanism. Considering Energy Storage System (ESS) and Distributed Generation (DG). Transmission and distribution networks are modeled by DCLF and ACLF, respectively. Formulating the proposed model as MPEC and converting it to MILP. Abstract: Adopting strategic behavior in the wholesale electricity market can revolutionize the performance of the Distribution Company (DisCo) in the operation of the distribution network. Besides, the demand response program in real-time pricing (RTP) environment, which is practicable within the smart distribution network, has a significant positive impact on the strategic behavior of this company. In this paper, a new framework is proposed to develop the sell and purchase strategies for a strategic distribution company in the energy and retail markets. The DisCo in this paper is the owner and operator of the distribution system that can affect the price of the energy due to the ownership of conventional and energy storage systems (ESSs). The uncertainty associated with the demands within the distribution network is considered by sets of scenarios. Also, the elasticity of the demands, which pertains to the retail price, is taken into account in the demand response program. Retail energy prices are also determined for customers under the RTP scheme. The problem is modeled in the form of a bi-level optimization problem, the upper-level of which includes maximizing the profit from energy sales to consumers under the RTP scheme and managing the production of distributed generation (DG) units, amount of charging or discharging of the storage system and deciding about LC program. And the lower-level is a market-clearing of the wholesale market aiming at maximizing social welfare. The upper network (sub-transmission network) is modeled in the form of a DC load flow equations to consider the impact of power transmission limits. By converting the bi-level problem to MPEC model and linearizing it using the dual theory and KKT conditions to a MILP model, finally, the MILP model is solved using the GAMS software. The performance of the proposed model is shown in two case studies, based on the IEEE-33BUS distribution network, and the 3-bus and 14-bus sub-transmission networks. Simulations investigate the impact of the strategic behavior of the DisCo on the financial and technical aspects of its operations. Simulations also indicate that the proposed model is an appropriate tool for analyzing the performance of the strategic DisCo in the wholesale and retail energy markets. Also, using the proposed approach can result in increasing of DisCo's profit, while declining in wholesale prices and load interruptions.